Physical Environmental Factors of The House and Smoking Habit on Acute Respiratory Infections in Toddlers 0-5 years in Buliang District Batam City - Novela Sari; Elvi Sinarsi; Ahmadi Ahmadi; Risky Cyndythia Sukarno (Publikasi Indonesia, 2024)
Acute Respiratory Infection (ARI) is an infection that occurs in the respiratory tract, both the upper and lower respiratory tract. This study aims to determine the relationship between physical home environment factors and smoking habits on ARI complaints in toddlers in Buliang, Batam City. The type of research used is quantitative with a cross-sectional research design. The sample in this study were mothers who had children aged 0-5 years. The sampling technique used was accidental sampling. The results of the chi-square test analysis showed that there was a relationship between room humidity and ARI complaints in toddlers (ρ-value = 0.000), there is no room lighting with ARI complaints in toddlers (ρ -value = 0.207), wall conditions and ARI complaints in toddlers (ρ -value = 0.037), smoking habits with ARI complaints in toddlers (p-value = 0.017) and there is no relationship between floor conditions and ARI complaints in toddlers (ρ-value = 0.121), ceiling condition with ARI complaints in toddlers (ρ -value = 0.906).